EXPLORATION OF AGILE LEADERSHIP STYLE AND TRAINING ON THE PERFORMANCE OF THE FAMILY ASSISTANCE TEAM’S (TPK) WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AS AN INTERVENING VARIABLE - Malasari, Diana Ruspita; Thamrin, Mohammad; Sanosra, Abadi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The aim of the research being developed was to test and analyze the effect of agile leadership and training on Organizational Citizenship Behavior (OCB), the effect of Organizational Citizenship Behavior (OCB) on the performance of Family Assistance Team cadres, and the effect of agile leadership and training on the performance of Family Assistance Team cadres both directly and indirectly with Organizational Citizenship Behavior (OCB) as an intervening variable. Method: Research design used descriptive and quantitative research methods. The research population was the entire Team 1 Cadre of the Family Assistance Team in 50 Villages/Subdistricts of Stunting Locus in Jember Regency, totaling 150 people. The sampling method used a saturated sampling technique (census). The data analysis technique used is Partial Least Square (PLS) using the WarpPLS 7.0 application. Results: Findings research shown that agile leadership and training has significant effect on the Organizational Citizenship Behavior (OCB). Organizational Citizenship Behavior (OCB) has significant effect on the performance of Family Assistance Team cadres. Agile leadership and training has significant effect on the performance of Family Assistance Team cadres both directly and indirectly with Organizational Citizenship Behavior (OCB) as an intervening variable. Novelty: This research is a development of theory and similar previous research which is reference material as a reference to compare whether previous research and theory can be used as a reference in improving performance in different places.